Variability of soil physical indicators imposed by beech and hornbeam individual trees in a local scale - YAHYA KOOCH; SEYED MOHSEN HOSSEINI; SEYED MOHAMMAD HOJJATI; ASGHAR FALLAH (Society for Indonesian Biodiversity, 2013)
Kooch Y, SM Hosseini, Hojjati SM, Fallah A. 2013. Variability of soil physical indicators imposed by beech and hornbeam individual trees in a local scale. Biodiversitas 14: 25-30. The objective of our study was to determine if soil physical indicators could be related to the influence of the individual trees in stands of mixed species growing on steep slopes in the Hyrcanian forests of Iran. Research was conducted in a forest dominated by beech 2 cross section. The result of this research showed that bulk density was significantly greater under beech than under hornbeam. This character tends to be less in 0-15cm depth than in 15-30cm and 30-45cm depths. Variable amounts of this character were found among diameter classes of beech and hornbeam also. Silt and clay were significantly greater under hornbeam than under beech. Moisture was significantly higher under beech than under hornbeam, whereas soil depths and diameter classes did not show any significant difference. Current research has shown that the influence of individual trees with different diameter classes can be detected in forest floors and upper minerals soil layers even under mixed stands in steepy sloping landscapes. This subject should be considered in natural forests management.